Penerapan Loose Parts terhadap Kreativitas Anak Usia Dini selama Belajar dari Rumah - Siti Rohmatun; Erika Setiyani; Fulka Rohfirsta; Dewi Fitamaya; Rohmatun Nisa; Muhammad Nofan Zulfahmi (Journal of Education and Teaching (JET), 2021)
During the current pandemic, face-to-face learning is abolished based on BDR (Learning From Home) activities. Children will be interested in BDR activities if they are packaged in the form of activities that explore children's creative abilities. Loose Parts-based learning is one of the media that can influence children's creativity programs, and later children will be able to think critically, analytically, creatively, and innovatively. The purpose of this study was to determine the application of Loose Parts to children's creativity during BDR. The research method used is descriptive qualitative method with the respondents being TK B students at TK Pertiwi 12.08 Papasan-Bangsri Jepara which collected 20 children. The results of the study concluded that children were interested in playing with various objects contained in the Loose Parts media. They are able to be creative with Loose Parts media that has been provided by parents, and children are also able to develop creativity from the results of the playing process using Loose Parts during BDR.